Sezonowość odpływu z wybranych zlewni karpackich = Seasonality of outflow in selected Carpathian catchments - Jokiel, Paweł; Tomalski, Przemysław (IGiPZ PAN, 2017)
This article details an analysis of seasonality of outflow carried out for 12 Carpathian catchments. The latter were selected in such a way as to fully represent various conditions of outflow formation in the Carpathian Mountains, i.e. the region of Poland in which hydrological processes are most dynamic. Daily series of discharges for the years 1951-2010 provided the basis for the research, albeit with the series lengths used in analyses of particular rivers varying in length from 40 to 60 years. In the case of each water-gauge section selected, calculations were made for the seasonality index (IS), time of concentration coeffi cient (WPK), outflow concentration index (GMO) and half-outflow term index (TPO). Multiannual variability and mutual correlation coefficients for the above parameters were also calculated, with these characteristics together describing various aspects to the seasonality of river outflow. The results of the research conducted show that values for the mean seasonality indexes characterising the outflow in Carpathian catchments are slightly lower than those calculated for amounts of precipitation. In addition, their spatial differentiation is relatively weak, while their variability over time is distinctly high. The mean time of concentration coefficient (WPK) for the Carpathian catchments does differ markedly from place to place, occurring between 4th Apri l and 3rd June. However, in the cases of the rivers draining the western part of the Beskid Mountains and Tatras, the outflow concentration occurs relatively late (after 5th May), while it is relatively early (before 5th May) in the cases of the rivers in the eastern part of the Beskids. The long-term variability of WPK in the Carpathian Mountains is less than half as great as that characterising the seasonality index (25.2% to 55.7% on average), though no significant trends could be noted for long-term series of those characteristics. Timing related to Oliver’s concentration coefficient (GMO) reveals aspects of seasonality similar to those presented by Markham’s seasonality index (IS). Due to this fact it would be more appropriate to name it an “outflow seasonality index” rather than an “outflow concentration index”. Mean multiannual half-outflow terms (TPOśr) in the Carpathian catchments are strongly diversified and appear between 15th April and 21st May. Low TPOśr was noted in rivers of a nival-pluvial and nival well-shaped regime. Low TPOśr was found with the pluvial-nival regime. The spatial differentiation to the multiannual variability of TPOśr in the Carpathian Mountains is limited. It is most limited in the case of rivers in the Tatra Mountains. Statistical analyses of multiannual series for all the seasonality parameters examined show that, in the Carpathian area, the seasonal structure to the outflow is relatively stable over the long term (given a lack of significant trends), with year-to-year fluctuations and changes being random in nature. The relative mean mass diagram curve for Carpathian catchments has two points of inflection confirming the nival-pluvial or pluvial-nival regimes. The regional curve offers a very effective presentation of the seasonal distribution of outflow in the Carpathian Mountains.
24 cm
Keywords: seasonality; river outflow; Carpathians